AN EVALUATION OF BALANCE DIET AND EATING PRACTICES OF UNIVERSITY STUDENTS IN PESHAWAR, PAKISTAN - Shahab Shah; Mujahid Ahmad; Nasrullah Dahani; Haq Nawaz khokhar (Scholar Express Journals, 2021)
The term balanced diet is in actual the technique of food intake in which the body is provided with all the required nutrients, vitamins and the minerals, those are required to maintain the correct functionality of cells, tissues and other body organs. Many health problems are directly linked to a diet which is lacking in nutrients, which afterwards arises problems ranging from lack of energy and tiredness to serious health problems which highly affects the functionality of vital organs and its decrease of growth and improvement. The amount of energy gained from the intake of food has a unique number of calories which highly depends on the selection of food. To evaluate the balance diet and eating practices in university students. Cross sectional study design and consecutive sampling technique was used. A sample size of 60 participants were included the data is collected from Abdul Wali khan university students of different departments. The study recruited 60 participants that there is high frequency of students with normal Body mass index and have enough knowledge about nutrition but the frequency of the balance diet in university students is low which is about 24 with the percentage of 40%. This study was mainly based on evaluating the balanced diet and eating practices in university students. The data indicated that most of the students were normal body mass index (BMI) shows that they have enough knowledge about nutrition and diet. our study included sixty participants the study was limited to the Abdul Wali Khan University students. This study also shows a high percentage of normal participants with a low percentage of obese
Keywords: Balanced diet; Eating practices; Peshawar; Pakistan